Preparation and characterization of silk fibroin as a biomaterial with potential for drug delivery - Zhang Hao; Li Ling-ling; Dai Fang-yin; Zhang Hao-hao; Ni Bing; Zhou Wei; Yang Xia; Wu Yu-zhang (Journal of Translational Medicine, 2012)
Abstract Background Degummed silk fibroin from Bombyx mori (silkworm) has potential carrier capabilities for drug delivery in humans; however, the processing methods have yet to be comparatively analyzed to determine the differential effects on the silk protein properties, including crystalline structure and activity. Methods In this study, we treated degummed silk with four kinds of calcium-alcohol solutions, and performed secondary structure measurements and enzyme activity test to distinguish the differences between the regenerated fibroins and degummed silk fibroin. Results Gel electrophoresis analysis revealed that Ca(NO3)2-methanol, Ca(NO3)2-ethanol, or CaCl2-methanol treatments produced more lower molecular weights of silk fibroin than CaCl2-ethanol. X-ray diffraction and Fourier-transform infrared spectroscopy showed that CaCl2-ethanol produced a crystalline structure with more silk I (α-form, type II β-turn), while the other treatments produced more silk II (β-form, anti-parallel β-pleated sheet). Solid-State 13C cross polarization and magic angle spinning-nuclear magnetic resonance measurements suggested that regenerated fibroins from CaCl2-ethanol were nearly identical to degummed silk fibroin, while the other treatments produced fibroins with significantly different chemical shifts. Finally, enzyme activity test indicated that silk fibroins from CaCl2-ethanol had higher activity when linked to a known chemotherapeutic drug, L-asparaginase, than the fibroins from other treatments. Conclusions Collectively, these results suggest that the CaCl2-ethanol processing method produces silk fibroin with biomaterial properties that are appropriate for drug delivery.